ANALYTIC STUDY FOR THE ATTACKING CONDITION OF IRAQI FOOTBALL TEAM PARTICIPATED IN THE ARABIAN GULF CUP 2023 PLAYERS - Assist.lecturer Zeyad Ahmad Diab (Scholars Digest Publishing, 2023)
The researcher used the descriptive approach, and the research sample was the matches of the Iraqi team participating in the Arabian Gulf Championship 2023, and there were (5) matches, and then all of them were analyzed. Various tools and devices and an analysis form were used. The attack is counted when the ball crosses the center line and the Iraqi player is in control of it. The researcher displayed the match on the calculator screen in order to calculate the number of successful and failed repetitions of each attack.The research aims to: Identifying the level of the offensive side of the players of the Iraqi national team participating in the 2023 Arabian Gulf Football Championship. The researcher concluded:: There were no significant differences between the two halves of the matches.There was a difference in the offensive aspect of the field and midfield during the matches in the tournament.The researcher recommended: The need to conduct similar research on the offensive and defensive aspects of all Iraqi teams and competing teams as well.Forming an academic and experienced technical committee in the Central Iraqi Football Federation that will analyze, follow up, and provide information according to scientific foundations for various aspects of the game and for all Iraqi teams.
Keywords: analytical study- Offensive mode - Arabs Gulf cup2023.